APLIKASI PENGELOLAAN NILAI MAHASISWA BERBASIS WEB (OBYEK : AKBID UNISKA KENDAL) (Information Technology and Telematics, 2014)
Abstract- The problem faced by Akbid Uniska Kendalin value management including the number of students whohave to queue up to ask for the resume value of course, becauseno information of value subjects terbaharuinya become a majorproblem because when a student is not necessarily asking for aresume value, the value of the course and a cumulative GPA ofstudents has been updated. Limited human resources andcounters were opened by the student academic servicesdepartment cause long queue so it is not efficient and effectiveuse of time, effort, and costs and disrupt academic activities ofthe students System development method used in this study iscomposed of a waterfall system startup, system analysis, systemdesign, system implementation, system testing. System designusing OOD which consists of a use case diagram, activitydiagram, sequence diagram and class diagram. Makingprograms using PHP and MySQL. The end result of thisresearch is the application has been successfully made themanagement of student grades Akbid Uniska Kendal that canbe used to manage the value of the courses that students can beupdated regularlyKeywords - Value, Waterfall, Uniska Kendal